Application of e-marketing by small-medium housing developer companies in Kelantan, Malaysia. - M. Mohd Rosli, M. Z. Normayuni; Mohd Nazri, M. (Universiti Sains Malaysia, 2014)

(untitled)
Global competition among the players in the housing and construction industry has pushed the companies to be more surviving and struggling for their long term competitiveness and hence;identifying a more innovative marketing strategy. In this context, e-marketing has been considered as one of the main aspects of marketing strategies among the companies, whereby the internet as the main vehicle.